Pemanfaatan Tumbuhan pada Upacara Adat Tumpang Negeri Suku Melayu di Keraton Ismahayana Landak - Irwan Lovadi, Uswatun Hasanah, Riza Linda (Universitas Tanjungpura, 2014)
Traditional Ceremony Tumpang Negeri is a tribal ritual of Malayan people that utilizes plants to prevent misfortune so that people of Landak Regency might be averted from menaces and that Landak egency might be a prosfer, safe, and peacefull land. The aim of this research was to investigate the plant spesies and their utilization in Tumpang Negeri. This research was conducted from January to March 2014. The method of respondence selection that used in this research was snowball. The result of this research shows that there are 23 plant species which belong to 12 families, have been used in Tumpang Negeri Ceremony. Most of the plants used belong 3 families which are Poaceae (5 species), Arecaceae (4 species), and Zingiberaceae (4 species). The plants are used as materials for making traditional snacks, rafts, and tumpang for offerings. Part of the plants that mostly used are the fruits (45 %), leaves (32 %), roots (18 %), and stems (5 %). The plants were harvested mostly from the forest (35 %), the botanical gardens (31 %), the home garden (30 %), and the fields. Every plant species used in Traditional ceremony tumpang Negeri has specifik meanings.